The Importance of Emotional, Spiritual Intelligence, and Self Efficacy on The Principal’s Performance in Sekolah Penggerak Program Based on Merdeka Curriculum - Eka Hendi Andriansyah; Mohamad Arief Rafsanjani; Dyah Nugraheny Priastuti (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze the importance of emotional, spiritual intelligence, and Self Efficacy on the performance of school principals in Sekolah Penggerak that use the Merdeka curriculum. Based on initial observations, it was found that there was a lack of emotional and spiritual intelligence in the principal, which hindered the effectiveness of the process of implementing the self-development of a principal. This study used the literature review method. The instruments used were national and international journals, reference books, and unstructured interviews for analysis using thematic analysis. The results showed that the Sekolah Penggerak was an effort to improve the quality of schools through holistic learning outcomes starting with High-Quality Human Resources (principals and teachers). Improvements were made through 5 interventions to schools to increase the capacity of Human Resources. Self-efficacy as part of emotional and spiritual intelligence can form school principals as leaders, planners, supervisors to evaluators in schools who are confident and think ahead. This intelligence can make a school principal confident in planning work programs, strongly committed, able to carry out programs well, and collaborate with teachers and administrative staff to achieve the school's goal of producing students to become Pancasila student profiles.